2016
DOI: 10.1007/s11664-016-4532-3
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Synthesis, Characterization, Morphological Control, and Photocatalyst Application of ZnWO4 Nanoparticles

Abstract: Zinc tungstate nanoparticles have been successfully synthesized by a precipitation method in the presence of different polymeric surfactants. This study aimed to investigate the effect of different solvents and polymeric surfactants such as carboxymethyl cellulose, polyethylene glycol, and polyvinyl alcohol on the morphology, particle size, and crystal structure of the final product. The as-synthesized products were characterized by powder x-ray diffraction analysis, scanning electron microscopy, ultraviolet-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(24 citation statements)
references
References 29 publications
(32 reference statements)
1
23
0
Order By: Relevance
“…The results indicated that the band-gap values of FeWO 4 are correlated with specific morphologies. Hosseinpour-Mashkani and co-workers [ 75 ] synthesized ZnWO 4 nanoparticles with different sizes through a precipitation route using different polymeric surfactants. The photocatalytic degradation experiments of MO demonstrated that the ZnWO 4 with the smallest size of 27 nm exhibited the highest photoactivity, compared with other ZnWO 4 samples under UV light illumination.…”
Section: Strategies For Enhanced Photocatalytic Activitymentioning
confidence: 99%
“…The results indicated that the band-gap values of FeWO 4 are correlated with specific morphologies. Hosseinpour-Mashkani and co-workers [ 75 ] synthesized ZnWO 4 nanoparticles with different sizes through a precipitation route using different polymeric surfactants. The photocatalytic degradation experiments of MO demonstrated that the ZnWO 4 with the smallest size of 27 nm exhibited the highest photoactivity, compared with other ZnWO 4 samples under UV light illumination.…”
Section: Strategies For Enhanced Photocatalytic Activitymentioning
confidence: 99%
“…Among them, various metal oxides have been used as supercapacitor active substances and in this family, binary oxides such as metal tungstate have attracted particular attention and a lot of research have been conducted in different field. Binary oxides display excellent characteristics in different area especially as high supercapacitive efficiency and good functional features including large specific capacitance, excellent cyclic performance and good rate capability . The aim of present study was to synthesizing cerium (III) tungstate nanoparticles through a precipitation route, investigating the composition and morphology of the product using different analytical techniques, as well as their supercapacitive properties through electro‐analytical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Another appealing n-type semiconductor is WO3 which has also been extensively studied for catalysis [8]. Bearing a smaller optical band gap of ~ 2.6 eV (exc ~ 475 nm), WO3 enables higher light harvesting in visible regime than TiO2 [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Another appealing n-type semiconductor is WO3 which has also been extensively studied for catalysis [8]. Bearing a smaller optical band gap of ~ 2.6 eV (exc ~ 475 nm), WO3 enables higher light harvesting in visible regime than TiO2 [8][9][10]. In spite of photocorrosion issue which leads to the formation of W 3+ and decreases its catalytic activity, the band position is also favorable for oxidation reactions on the surface [11,12].…”
Section: Introductionmentioning
confidence: 99%